Enabling collective action for smallholder market access - CGIAR Program on Collective Action and Property Rights (International Food Policy Research Institute, 2010)
Discussions about poverty reduction inevitably include the need to increase small landholders' ability to participate successfully in market exchanges. However, smallholders must be aware of new opportunities and challenges brought about by changes in the global agricultural economy. Prominent among these changes is the growing demand for higher value and for processed foods, as well as the increasing number of supermarkets as outlets for farm products that have in turn altered procurement systems and made quality and safety standards more stringent.